Urban Mobility, Accessibility, And Tourism Flows: A Mobility Justice Perspective In Jakarta - Salsabilla Retno Sedah Mirah Murcahyaningrum; Ichwan Aulia Heriza; Wilda Fitri Tanga; Harry Florentinus; Fetty Asmaniati; Myrza Rahmanita (Sumber Belajar Sejahtera, 2026)
This study examines how urban mobility, accessibility, and mobility justice shape tourism flows in Jakarta, a rapidly developing metropolitan destination. It investigates the gap between planned accessibility in transport infrastructure and the actual accessibility experienced by tourists and local residents in their daily mobility practices. Data were collected through in-depth interviews with tourism and transport authorities, community representatives, and visitors, supplemented by field observations and analysis of relevant policy documents. The data were analyzed thematically to identify patterns related to accessibility, walkability, last-mile connectivity, and mobility justice. The findings reveal that despite improvements in multimodal transport systems and pedestrian infrastructure, accessibility remains uneven across the city. Challenges such as inadequate last-mile connectivity, discontinuous walkways, and inconsistent barrier-free design continue to shape visitor movement and reinforce mobility inequalities, particularly for residents of informal settlements and vulnerable groups. The novelty of this research lies in integrating mobility justice into urban tourism analysis by linking transport planning intentions with lived mobility experiences in a Global South megacity context. This study highlights the need to embed mobility justice principles in urban tourism and transport planning to ensure inclusive, sustainable, and human-centered development in Jakarta.